Improving Memory Inhibition: A Study of Retrieval Induced Forgetting, Executive Control, and Chronic Aerobic Exercise - Padilla, Concepción; Andres, Pilar; Bajo, Teresa (Frontiers in Behavioral Neuroscience, 2018)
Chronic aerobic exercise is being established as a way to enhance executive functions and prevent cognitive decline. In the current study, we aimed at investigating whether chronic aerobic exercise would also modulate long-term memory retrieval under the context of the Retrieval Practice Paradigm. According to Anderson et al. (1994), the retrieval of certain information may decrease the access to other related information inducing forgetting. Interestingly, it has been shown (Román et al., 2009) that this process is mediated by the level of attentional resources. In order to test if chronic aerobic exercise benefits attentional resources, we applied the Dual Retrieval Practice Task. This task explores the effects of memory retrieval on forgetting information directly related to the items that have been previously retrieved, but also studies the involvement of attentional resources on this type of forgetting (retrieval induced forgetting). This task alternates memory retrieval practice with an updating task in order to load attentional resources. Two groups of physically active and sedentary young participants were evaluated. The results showed that while active participants were able to show retrieval induced forgetting despite the overload of the attentional resources, sedentary participants were not. These results are discussed in terms of the modulatory role of chronic aerobic exercise on executive control and retrieval induced forgetting.